Mutational analysis defines the 5′-kinase and 3′-phosphatase active sites of T4 polynucleotide kinase - Wang, Li Kai (Oxford University Press, 2002)
T4 polynucleotide kinase (Pnk) is a bifunctional 5′-kinase/3′-phosphatase that aids in the repair of broken termini in RNA by converting 3′-PO(4)/5′-OH ends into 3′-OH/5′-PO(4) ends, which are then sealed by RNA ligase. Here we have employed site-directed mutagenesis (introducing 31 mutations at 16 positions) to locate candidate catalytic residues within the 301 amino acid Pnk polypeptide. We found that alanine substitutions for Arg38 and Arg126 inactivated the 5′-kinase, but spared the 3′-phosphatase activity. Conservative substitutions of lysine or glutamine for Arg38 and Arg126 did not restore 5′-kinase activity. These results, together with previous mutational studies, highlight a constellation of five amino acids (Lys15, Ser16, Asp35, Arg38 and Arg126) that likely comprise the 5′-kinase active site. Four of these residues are conserved at the active sites of adenylate kinases (Adk), suggesting that Pnk and Adk are structurally and mechanistically related. We found that alanine substitutions for Asp165, Asp167, Arg176, Arg213, Asp254 and Asp278 inactivated the 3′-phosphatase, but spared the 5′-kinase. Conservative substitutions of asparagine or glutamate for Asp165, Asp167 and Asp254 did not revive the 3′-phosphatase activity, nor did lysine substitutions for Arg176 and Arg213. Glutamate in lieu of Asp278 partially restored activity, whereas asparagine had no salutary effect. Alanine substitutions for Arg246 and Arg279 partially inactivated the 3′-phosphatase; the conservative R246K change restored activity, whereas R279K had no benefit. The essential phosphatase residues Asp165 and Asp167 are located within a (165)DxDxT(169) motif that defines a superfamily of phosphotransferases. Our data suggest that the 3′-phosphatase active site incorporates multiple additional functional groups.